Lasting Symptoms After Esophageal Resection (LASER): European Multicenter Cross-sectional Study. Issue 2 (February 2022) - Markar, Sheraz R.; Zaninotto, Giovanni; Castoro, Carlo; Johar, Asif; Lagergren, Pernilla; Elliott, Jessie A.; Gisbertz, Suzanne S.; Mariette, Christophe; Alfieri, Rita; Huddy, Jeremy; Sounderajah, Viknesh; Pinto, Eleonora; et al.
Abstract : Objective: To identify the most prevalent symptoms and those with greatest impact upon health-related quality of life (HRQOL) among esophageal cancer survivors. Background: Long-term symptom burden after esophagectomy, and associations with HRQOL, are poorly understood. Patients and Methods: Between 2010 and 2016, patients from 20 European Centers who underwent esophageal cancer surgery, and were disease-free at least 1 year postoperatively were asked to complete LASER, EORTC-QLQ-C30, and QLQ-OG25 questionnaires. Specific symptom questionnaire items that were associated with poor HRQOL as identified by EORTC QLQ-C30 and QLQ-OG25 were identified by multivariable regression analysis and combined to form a tool. Results: A total of 876 of 1081 invited patients responded to the questionnaire, giving a response rate of 81%. Of these, 66.9% stated in the last 6 months they had symptoms associated with their esophagectomy. Ongoing weight loss was reported by 10.4% of patients, and only 13.8% returned to work with the same activities. Three LASER symptoms were correlated with poor HRQOL on multivariable analysis; pain on scars on chest (odds ratio (OR) 1.27; 95% CI 0.97–1.65), low mood (OR 1.42; 95% CI 1.15–1.77) and reduced energy or activity tolerance (OR 1.37; 95% CI 1.18–1.59). The areas under the curves for the development and validation datasets were 0.81 ± 0.02 and 0.82 ± 0.09 respectively. Conclusion: Two-thirds of patients experience significant symptoms more than 1 year after surgery. The 3 key symptoms associated with poor HRQOL identified in this study should be further validated, and could be used in clinical practice to identify patients who require increased support. Abstract : Supplemental Digital Content is available in the text